THE EFFECT OF SHRIMP TRADE COMPETITIVENESS ON SUSTAINABLE ECONOMICS - Tety Rachmawati; Fahmi Tarumanegara; Rahayu Lestari (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
Shrimp is one of the main commodities in the global fisheries trade. As the value and volume of shrimp trade continues to increase, factors that shape the competitiveness of shrimp trade should contribute to a sustainable economy. This study will use the SEM (Structural Equation Model) test method to examine the effect of shrimp export competitiveness on the sustainable economies of countries. Additional analysis will also involve cluster analysis (K-Mean Cluster or Hierarchical Cluster) to map countries according to the IDSEU index and their sustainable economic performance. The results of the study show that the variables of state and business governance have a high value in influencing sustainable economic variables. The test results also show that countries that are major players in global shrimp trade have high competitiveness but show low sustainable economic performance. Therefore, the role of the government is very necessary, not only to support competitiveness improvement aimed at increasing exports but also to continue to adhere to the principles of sustainable economics.